2020
DOI: 10.1002/jcp.29975
|View full text |Cite
|
Sign up to set email alerts
|

SPARC is a key mediator of TGF‐β‐induced renal cancer metastasis

Abstract: Aberrant expression of transforming growth factor-β1 (TGF-β1) is associated with renal cell carcinoma (RCC) progression by inducing cancer metastasis. However, the downstream effector(s) in TGF-β signaling pathway is not fully characterized. In the present study, the elevation of secreted protein acidic and rich in cysteine (SPARC) as a TGF-β regulated gene in RCC was identified by applying differentially expressed gene analysis and microarray analysis, we further confirmed this result in several RCC cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…4 D) and newly identified RANBP3L dependent genes like Sparc , Col4a1 and Col4a2 are upregulated, a feature already reported for RCC development and progression [ 57 , 58 ]. Interestingly, SPARC was described as key mediator of TGF-β-induced metastasis in RCC cell lines [ 57 ] corroborating the morphological and phenotypical changes we observed in RANBP3L-deficient cells. Further, the ectopic expression of Ranbp3l in the KIRC cell lines 786-0, Caki-1 and Caki-2 attenuated their cell migration behavior and reduced the cell proliferation in Caki-1 and Caki-2.…”
Section: Discussionmentioning
confidence: 89%
“…4 D) and newly identified RANBP3L dependent genes like Sparc , Col4a1 and Col4a2 are upregulated, a feature already reported for RCC development and progression [ 57 , 58 ]. Interestingly, SPARC was described as key mediator of TGF-β-induced metastasis in RCC cell lines [ 57 ] corroborating the morphological and phenotypical changes we observed in RANBP3L-deficient cells. Further, the ectopic expression of Ranbp3l in the KIRC cell lines 786-0, Caki-1 and Caki-2 attenuated their cell migration behavior and reduced the cell proliferation in Caki-1 and Caki-2.…”
Section: Discussionmentioning
confidence: 89%
“…FN1 is a glycoprotein expressing gene, encoding an important component of the extracellular matrix, which could interact with the integrin receptor[ 19 , 20 ]. SPARC is a protein-coding gene rich in cysteine and could be expressed in fibroblasts, osteoblasts, chondrocytes, epithelial cells, and platelets[ 21 ]. Previous studies have shown a significant role of the two proteins, FN1 and SPARC, in the regulation of various physiological and pathological processes, including tissue reconstruction, cell migration, and morphogenesis[ 22 - 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that SPARC can induce brain infiltration during BM. Bao et al reported that SPARC was a key mediator of the TGF-β signaling pathway and promoted invasion and metastasis of renal cell carcinoma [76]. In lung squamous cell carcinoma, COL1A1 overexpression in the microenvironment is highly correlated with lymph node metastasis [77].…”
Section: Discussionmentioning
confidence: 99%